NEUROPROTECTOR CHARACTERISTICS OF ADEMOL IN THE REGENERATIVE PERIOD OF EXPERIMENTAL ISCHEMIC INSULT - A. A. Khodakovskiy (Медицинский вестник Юга России, 2013)
Purpose: To describe the differential features of Essential Tremor and Parkinson Disease. Purpose. Characterized efficiency of ademol in the regenerative period of ischemic insult according neuromorphological changes in the cortex of the brain of the rats.Materials and methods. Experimental therapy of the rats with cerebral infarction (bilateral carotid occlusion) by derivate of adamantan 1-adamantilethyloxy-3-morpholino-2 propanol hydrochloride (under conventional name ademol) was conducted in dose 2 mg/kg intraabdominal in the treatment mode (in an hour after modeling of insult and further after every 24 hours during 21 days).Results. In the course of conducted investigations were established that in the regenerative period of the modeling acute disorder of cerebral circulation (bilateral carotid occlusion) takes place increasing of quantity and density of destructively changed neurons parallel with decreasing of area and density of morphologically undamaged neurons and also contents of nucleinic acids in them. Therapeutic course injection of ademol by the scheme as outlined above contributes to the normalization of micromorphometric characteristics of somatosensory cortex of the brain, that is manifested by conservation of density and area of structurally undamaged neurons on the background of decreasing of density of neuroglia and destructively changed nervous cells.Summary. Ability of ademol to maintain cytoarchitectonics of the brains’ cortex indicates the presence of cerebroprotective characteristics of it and justifies the perspective of development of new cerebroprotector on its base.